A theoretical criterion on the initiation type of oblique detonation waves. (January 2022) - Shi, Xinxing; Xie, Haopin; Zhou, Lin; Zhang, Yining
Abstract: Predicting the initiation type of oblique detonation waves (ODWs) is critical to the application of ODWs in engine, but there is still no fully analytical criterion on the initiation type. In this study, a theoretical criterion is proposed to predict the initiation type, whose physical foundation is compression wave convergence observed recently. The criterion depends on the ratio of two characteristic lengths, the height of compression wave intersection point, H CW, and the corresponding height of oblique shock wave (OSW) at the same x -location, H OSW . If the ratio is below 1, the compression wave converges quickly to induce abrupt initiation; otherwise, slow compression wave convergence leads to smooth initiation. Because these two parameters could be calculated theoretically, this is the first fully analytical criterion independent of numerical or experimental parameters. Numerical results demonstrate that the criterion performs well in hydrogen–air mixtures corresponding wide flight conditions. Further examinations in two kinds of hydrocarbon fuel-based mixtures under standard conditions demonstrates the universality of this criterion. Highlights: A theoretical and universal criterion is proposed to predict initiation type. The physical model of compression wave convergence is adopted for the criterion. Criterion predicts well in a hydrogen–air mixture in a wide ﬂight conditions. Criterion is applicable to hydrocarbon fuel-based mixtures under standard conditions.